From giving orders to engaging in dialogue: Military norms being challenged at the Swedish riding school. (June 2018) - Thorell, Gabriella; Hedenborg, Susanna; Stråhlman, Owe; Morgan, Karin
Equestrian sport is one of the largest sports among young girls in Sweden. A majority of these girls get their riding education at riding schools that provide horses and instructors. Previous research has pointed out that the Swedish riding school is characterised by a traditional stable culture that originated in army practices. Presently Swedish children and youth sport at large are undergoing a change driven by increased commercialisation and individualisation. The aim of this article is therefore to explore and analyse how Swedish riding instructors perceive and experience their professional role in regards to these changes. Interviews with 10 riding instructors have been analysed using a constructivist approach of Grounded theory, as well as institutional theory and institutional economic theory. It was discovered that the riding instructors, due to an economic recession, feel that the institutional arrangements of the riding schools have become governed by the economy. The riding instructors thus feel impelled to change and adapt to new teaching styles – from instruction characterised by giving orders to teaching characterised by dialogue. This study illustrates how economic challenges require continuous development of the riding instructors' pedagogical ability, and have made them more aware of their profession, its historical heritage and norms.